From Europe to the Chaco-Paraguayan frontier. The Jesuit Brothers: Biographical trajectories, war and global histories in the 17th century - Svriz Wucherer, Omar (Ciencia Nueva, revista de Historia y Política, 2019)
This article aims to analyse the biographical trajectories of various Jesuit Brothers in the 17th century, such as Domingo de Torres, Antonio Bernal, among others. Most of them were born in Europe and were soldiers in numerous battles. They then joined the Society of Jesus and travelled to the Paraguayan Jesuit Missions where they taught the Guarani Indians how to use European firearms and tactics of war. In this way, the life of these Jesuit Brothers shows us the mechanisms by which the Spanish Empire negotiated and protected its frontiers with "non-state" agents (Jesuits) and local native populations (Guaraní Indians). This biographical view enables us to understand how frontier defences were constructed, and how the inter-imperial relationship as well as the military knowledge circulation functioned in the Spanish Empire.